Питоме і чуже в термінології: гармонія чи конфлікт? - Селігей, П.О. (№9, 2007)
The issue of the article is correlation of native words and adoptions in Ukrainian terminology. The necessity to critically reconsider excessive borrowings is substantiated as well as to use native elements more actively in creation of new scientific and technical terms.